Decreased level of consciousness in a child: recognition and management. (27th February 2020) - Patel, Neal; Nandakumar, Naveen; Heaton, Paul Anthony; Le Huray, Vicki; Paul, Siba Prosad
Abstract : A child presenting with decreased level of conscious (dLOC) is of great concern due to the wide range of possible causes, and potential for death or serious long-term sequelae. It is therefore vital that health professionals can recognise a child with dLOC quickly, intervene appropriately and escalate for senior review as a matter of urgency. This article provides an explanation for the mechanisms of decreased consciousness, outlines the different causative pathologies, and provides a simple and logical approach to the first-line recognition and management that a health professional may apply when faced with such a patient. Illustrative case studies have been included, to demonstrate how children with dLOC may present in clinical practice